Robust logistic regression to narrow down the winner’s curse for rare and recessive susceptibility variants - Kesselmeier, Miriam; Lorenzo Bermejo, Justo (Briefings in bioinformatics, 2017)
Abstract. Logistic regression is the most common technique used for genetic case-control association studies. A disadvantage of standard maximum likelihood est